(untitled) (Economics and region, 2022)
The article raises the problem of aggravation of economic, social, and environmental crises of various origins in the world. It was emphasized that the European Union is the global driver of innovative and global environmental initiatives, in particular the large-scale initiative of the European Green Deal, which should make Europe the first carbon-neutral continent in the world by 2050 and ensure the achievement of a fair, climate-neutral state, resource-efficient and competitive economy. The genesis and peculiarities of the circular economy as the main prerequisite for ensuring the sustainable development of all economic entities: the country, the region, and the enterprise, are studied. It has been established that the circular economy is gradually changing the traditional linear concept of the economy. The linear model of the economy is characterized by an approach where products are produced, used, and disposed of (take-make-dispose). The 3-R principle is decisive for the circular approach: 1) reduce: reduce the use of resources and give priority to renewable materials; 2) reuse: use products as efficiently as possible; 3) recycle: recover by-products and waste for further use in the economy. Approaches to determining the index for assessing the degree of circular economy integration have been studied: The Material Circularity Indicator (MCI), The Regional Circular Economy Index System (RCEIS), The Circular Economy Performance Index (CEPI), A Circular Economy Index for the Consumer Goods Sector (CEICGS), Circular Economy Development Index (CEDI). The results of the expansion of the circular economy for the EU are considered. It is justified that in the context of Ukraine’s European integration aspirations, the state needs to adapt to the circular economy’s requirements, considering the principles and goals, opportunities, and threats. The current state of Ukraine’s fulfillment of the requirements for joining the EU is assessed. It has been proven that in the post-war period, before Ukraine becomes a member of the EU, deepening of industry integration is necessary, increase in duty-free exports to the EU market; cancellation of non-tariff measures restricting trade with the EU. First of all, in this context, it is necessary to take into account one’s own national interests and the trade partner’s, in particular Ukraine’s institutional (regulatory) support for the EU initiative "European Green Deal" regarding the formation of Europe as a carbon-neutral continent and the gradual adaptation of the post-military national economy to the requirements of circular economics. The insufficient level of development of the circular economy in Ukraine caused by Russia’s ongoing unprovoked and unjustified aggressive war against Ukraine; the imperfection of the institutional environment; insufficient business motivation. The implementation of the principles of the circular economy in Ukraine requires a systematic and complex system restructuring, based on the legislative base, the introduction of innovative technologies, the digitization of production and trade processes, the financing of environmental initiatives, the stimulation of innovative environmentally friendly business models, the formation of environmental awareness in society and the formation of the habit of broader use of sustainable products and creating new ways of interaction between producers and consumers, stimulating the emergence and development of innovative professions.